The Impact of Social Media (SM) on Sport Marketing Strategy Development: A Case Study of Football Teams in Iraq - Ali Ismael Obaid; Kishore Kumar C K (Journal La Sociale, 2022)
The purpose of this study is to look into the impact of SM on the development of sport marketing strategies by football teams in Iraq. This study employed a quantitative approach, with data collected by a questionnaire. Questionnaire was sent to 200 people, and they were all contacted for responses. The findings of this study show that approximately 97.5% of respondents using SM, especially Facebook (32.5%) as the favorite over traditional media. Most of the SM users are of below 30 years of age (youngsters) and likely to spend roughly spending 2-5 hours on SM every day and remain active in posting messages to each other, pay attention to the advertisement of sports products and like to watch them too. Thus, developing SM tools is critical for football teams to succeed in their sports marketing strategy (MS) and build professional relationships with their fans. The football team must use SM as a powerful tool for developing its sports MS and capturing fans as an essential product. They should be able to use a variety of SM platforms.